Pencegahan Dan Pengendalian Hipertensi Melalui Pendidikan Kesehatan Pada Warga Desa Kungkai Baru Kabupaten Seluma - Meri Epriana Susanti; Emi Pebriani; Murwati Murwati; Sulastri Sulastri (Jurnal Dehasen Untuk Negeri, 2023)
Hypertension is an increase in blood pressure in the arteries. Where is Hiper which means excess, and Tensi which means pressure/tension, so hypertension is a disturbance in the circulatory system which causes an increase in blood pressure above the normal value (Musakkar & Djafar, 2021). Counseling about hypertension is very important to be given to people who are currently experiencing hypertension or who are at risk of experiencing hypertension, both pre-elderly and elderly. Therefore this counseling is given to increase knowledge to the public that hypertension itself is very dangerous if not handled, and after this counseling it is hoped that the community can prevent and control hypertension. And hypertension exercise is very important to control hypertension.